Implementasi Data Mining Klasifikasi Fuel Surcharge Menggunakan Algoritma Naive Bayes Studi Kasus PT Pelabuhan Indonesia (Persero) Regional 2 Tanjung Priok - Baidowi, Ahmad; Sutisna (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
In the application of fuel surcharge in PT Pelabuhan Indonesia (Persero) Regional 2 Tanjung Priok, it is necessary to display data that can help become the basis for the imposition of fuel surcharge from data on the movement of pilot vessels / tugboats which is the basis for the imposition of fuel surcharge in PT Pelabuhan Indonesia (Persero) Regional 2 Tanjung Priok, this research was conducted to help provide information to workers, Kesyahbandaran Otoritas Pelabuhan Utama and ship service users or shipping agents in more detail related to the imposition of fuel surcharge in the PT Pelabuhan Indonesia (Persero) Regional 2 Tanjung Priok environment, using data mining methods in fuel surcharge peneran as a consideration to make it easier to understand, easier to see and easier to operate. With this data mining method, it will help the company to become an important data and facilitate workers in the data collection section related to fuel surcharge in which there is a recap of the number of ship movements, the number of notes, the strength of groos tons (GT), house power (HP) of the ship and payment status. The use of data mining methods is expected to be a solution for workers in data collection and become a history of fuel surcharge collection within PT Pelabuhan Indonesia (Persero) Regional 2 Tanjung Priok.